-7/24, because you can just do this question in reverse to figure out an answer. (3/8 - 2/3)
I already a seed you when you asked this the first time. The answer is 3.
You multiply both sides by 50 and then you get this
(In the picture)
Answer:
there’s nothing there
Step-by-step explanation:
In this case, h(x) = sqrt(x) + 3
A. f(x)=x+3; g(x)=√x
B. f(x)=x; g(x)=x+3
C. f(x)=√x; g(x)=x+3
D. f(x)=3x; g(x)=√x
Again, you need to find a function f(x) that once evaluated in g(x) gives us h(x)
h(x) = g(f(x))
Looking at the options, the answer is C.
g(f(x)) = f(x) + 3 = sqrt (x) + 3 = h(x)